Species diversity and abundance of Euphylliidae (Cnidaria: Anthozoa:Scleractinia) corals in Tioman, Redang and Payar Islands, Peninsular Malaysia - Saad, Shahbudin; Khodzori, Mohd Fikri Akmal (Universiti Malaysia Sabah, 2017)
The number of endangered coral species is increasing over the past decades due to multiple stresses and threats. Euphylliidae corals are among the species heavily targeted for the marine aquarium trade due to their colourful appearance and aesthetic importance. However, their distribution in Peninsular Malaysia has not been thoroughly investigated. Present study aims to investigate the diversity and abundance patterns of euphylliid species at 36 reef sites in Marine Protected Areas of Tioman, Redang and Payar Islands. Video transect surveyed a total of 671 euphylliids individuals belonging to six species from three genera. The diversity and evenness indices of euphylliids were significantly higher (P<0.05) in Tioman compared to Redang and Payar Islands. Based on the total number of euphylliids recorded in the study areas, Euphyllia ancora (29.5%) was found to be the most dominant in Tioman, Plerogyra sinuosa (92.3%) in Redang and Physogyra lichtensteini (98.0%) in Payar. Current findings suggest that the combined factors of habitat heterogeneity, especially the reef morphology and substratum condition, and anthropogenic impacts have most likely influenced the distribution of this endangered coral species in Peninsular Malaysia.